Human development and human rights, two sides of the same coin - Rojas Rojas, Sonia Esmeralda (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this article was to reflect on two issues of great impact, transcendence and social importance: human development and human rights. For this, the genesis of the concept of development is exposed. Then the reflection continues around two major themes, economic growth and development. It then continues with two interesting debates, one referring to social reality and development, and the other to the relationship generated between development and human development. In addition, it seeks to discern about the relationship between human development and human rights. It is concluded that without the guarantee of human rights, it is inadmissible to speak of human development and that, without human development, what exists is an institutionalization of the violation of human rights.